THE INDONESIAN CRIMINAL CODE: UNREGULATED ADULTERY (AN OVERVIEW OF ISLAMIC CRIMINAL LAW) - Irfan Ardiansyah; Duwi Handoko; Beni Sukri (PENA LAW: International Journal of Law, 2022)
God created sexual intimacy to be enjoyed only in marriage. God has determined that Adam's children tend to commit adultery. This desire is inevitable, namely to commit adultery in the form of vision, adultery of the mouth in the form of narrative, adultery feelings through ideals and the desire to get it. However, it is the genitals who determine in adultery or not. The Indonesian Criminal Code does not view all non-marital sex relations as adultery. According to the Indonesian Criminal Code, adultery can only occur if sexual relations outside of marriage are carried out by people who are married. In addition, adultery in Indonesia cannot be threatened with punishment if there are no complaints from the victim who feel insulted or harmed, namely the husband or wife of the perpetrator.